Measurement the differences in Emotional Intelligence at students of theoretical and applied disciplines at the University of Damascus (Journal of Hama University, 2019)
The study aims to measure the differences in emotional intelligence by applying the emotional intelligence test of Bar-On and Parker, On a sample of students from the University of Damascus, consisting of 500 male and female students from the architectural and law faculties, of whom 200 are males and 300 are females. In order to identify whether there are differences in the average emotional intelligence scores among students of theoretical disciplines (law) and applied disciplines (architecture), between male students in the architectural and law faculties, and between female students in the architectural and law faculties, and between males and females in college Architecture, between males and females in law school, and in the research sample in a holistic manner.The study has the following results:• There are statistically significant differences in emotional intelligence between students of the Faculty of Architecture and students of the Faculty of Law in favor of students of the Faculty of Law.• The results show that there were statistically significant differences in emotional intelligence in the research sample according to the variable of the tutorial year in favor of the first year and the second year.• There are statistically significant differences in emotional intelligence between males and females in favor of females.